PENGEMBANGAN MEDIA PEMBELAJARAN INTERAKTIF FLIPBOOK BERBANTUAN CANVA UNTUK MENINGKATKAN PEMAHAMAN KONSEP SISWA PADA MATERI PEMANASAN GLOBAL DI KELAS X - Sari, Ciawulan; Purwanto, Andik; Medriati, Rosane (UNIB Press, 2025)
The purpose of this study is to produce a viable product in the form of the development of Canva-assisted Flipbook Interactive learning media to increase students' understanding of concepts in global warming material in class X. This research is also to describe the improvement of students' understanding of concepts in global warming materials after using Canva-assisted Flipbook Interactive learning media. The research method used is Research and Development by applying the ADDIE model. The instruments used in this study are questionnaires, observations, interviews and concept comprehension tests. The results of this study show that an average result of 89.58% was obtained in the very feasible category. Based on the results of the N-gain calculation obtained by the Pretest and Posttest, a result of 0.74 is included in the high category. So that it can be summarized based on research that has been conducted at SMA Negeri 2 Kota Bengkulu class X1, namely Interactive Flipbook media assisted by Canva to increase students' understanding of concepts on global warming materials developed is worthy of testing and increasing high understanding of concepts shows that Interactive Flipbook learning media assisted by Canva can improve students' understanding of concepts.